Analisis Dampak Penerapan Peraturan Pemerintah No 58 Tahun 2023 Terhadap Pemotongan Pajak Penghasilan Pasal 21 Pada Wajib Pajak Orang Pribadi - Fitria Novi Nuraini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research is to determine and analyze the impact of calculating PPh Article 21 for individual taxpayers on income received with deductions based on Government Regulation No. 58 of 2023. This research method uses a quantitative approach. The type of research is quantitative descriptive. The research data used in this research is secondary data in the form of tax reports that use the Tax Effective Rate (TER). And primary data is the result of observations carried out by researchers as support for this research data, such as interviews with individual taxpayers who have been deducted PPh Article 21 on salaries received using TER. The results of the research show that the salary and allowances that Mr. ABC continues to receive, are deducted from the PPh payable in different amounts, where in the December period the payment is smaller, because it has been reduced by the PPh payable which has been deducted in the January to November period. So the impact given to the implementation of Government Regulation No. 58 of 2023 has a positive impact, where the calculation period is greater but in the December period it is smaller.